# Factorise: 2x^{2 }+ 2x - 364.

A quadratic eqaution is in the the form of ax^{2 }+ bx + c = 0, where a is not equal to 0.

## Answer: The factorization of 2x^{2 }+ 2x - 364 is (x + 14) (x - 13).

Let's solve it step by step.

**Explanation:**

Factorization is the method to break the arithmetic algebraic equation in the product of its factors.

So, look at the factorization of 2x^{2 }+ 2x - 36.

2x^{2 }+ 2x - 364 = 2 ( x^{2 } + x - 182)

= x^{2 } + x - 182

As we know that 2, 7 and 13 are the factors of 182, we will break the middle term.

= x^{2 } + 14x - 13x - 182

= x (x + 14) - 13 (x + 14)

= (x + 14) (x - 13)